Circulating choline pathway nutrients and risk of moyamoya disease - Ge, Peicong; Zhao, Yaobo; Zhai, Yuanren; Zhang, Qian; Ye, Xun; Wang, Jia; Wang, Rong; Zhang, Yan; Zhang, Dong; Zhao, Jizong (Frontiers in Nutrition, 2022)
Background Circulating choline pathway nutrients play a critical role in first stroke and recurrent stroke. However, there is limited information available on the effects of choline pathway nutrients on the risk of moyamoya disease (MMD) and its subtypes. We investigated the association between circulating choline and betaine and the incident risk of MMD and its subtypes. Methods The case-control study enrolled 385 patients with MMD [i.e., 110 transient ischemic attack (TIA)-type MMD, 157 infarction-type MMD, and 118 hemorrhagic-type MMD] and 89 matched healthy controls. Results Serum choline and betaine were inversely related to the risk of MMD and its subtypes. The risk of MMD was decreased with each increment in choline level [per 1 μmol increase: odds ratio (OR), 0.756; 95% CI, 0.678–0.843] and betaine level (per 1 μmol increase: OR, 0.952; 95% CI, 0.932–0.972), respectively. When choline and betaine were assessed as quartiles, compared with the lowest quartile of serum choline and betaine levels, those in the highest quartile had a significantly decreased risk of MMD (choline, Q4 vs. Q1: OR, 0.023; 95% CI, 0.005–0.118; betaine, Q4 vs. Q1: OR, 0.058; 95% CI, 0.018–0.184). Conclusions Serum choline and betaine were associated with the decreased risk of MMD and its subtypes.